Countering Commoditization Through InnovationChallenges for European B2B Companies: B2B companies can use a Commoditization-Innovativeness Matrix to identify actions to counteract the pervasive threat of commoditization that exists in many B2B markets. Issue 4 (16th May 2021) - Goffin, Keith; Beznosov,, Aleksei; Seiler, Matthias
Abstract : Overview: B2B companies are an important part of the global economy, and traditionally they have relied on technological capabilities to compete. Currently, the B2B sector is under increasing pressure, as many B2B companies no longer have a technological advantage, and they also face commoditization. Companies see innovation as a way to compete against these challenges. Although product and process innovation are important in B2B markets, companies need other forms of innovation such as service and business model innovation to create a differentiated offering. B2B managers' views on the value of market research vary widely, and many are unaware that sophisticated techniques such as ethnography can effectively identify B2B customer needs. Our Commoditization-Innovativeness Matrix is a diagnosis tool that enables B2B companies to identify actions that can counter commoditization.